Follow-Up Evaluation Project. From July 1, 1981 to June 30, 1983. Final Report - Santa Fe Community Coll., Gainesville, FL.; Santa Fe Community Coll., Gainesville, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A project was undertaken to revise a model competency-based trade and industrial education program that had been developed for use in Florida schools in a project that was implemented earlier. During the followup evaluation, the project staff compiled task listings for each of the following trade and industrial education program areas: automotive; building construction; child development; cosmetology; clothing production and fashion merchandising; data processing; drafting; electrical construction; gasoline engine mechanics; graphic design technology; solar and heating, air conditioning, refrigeration, and ventilation; technical mathematics; and welding. Next, a project advisory committee and a group of local employers reviewed the task listings, made recommendations for changes in them, determined the occupational skills needed by students in each program area, identified the major outcomes for the program and for each course of study, and identified the entry-level skills and the minimum performance levels for the program and for each course of study. Generally, the followup project participants were quite pleased with the original curriculum development effort. (The bulk of this volume consists of program maps or task listings and sets of objectives for each of the 13 program areas mentioned above.) (MN)
Sponsoring Agency: Florida State Dept. of Education, Tallahassee. Div. of Vocational Education.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Air Conditioning; Auto Mechanics; Behavioral Objectives; Building Trades; Child Development; Clothing; Competence; Competency Based Education; Construction (Process); Cosmetology; Course Content; Curriculum Development; Data Processing; Drafting; Educational Needs; Educational Objectives; Electrical Occupations; Engines; Fashion Industry; Followup Studies; Graphic Arts; Heating; Job Skills; Mathematics Skills; Merchandising; Needs Assessment; Postsecondary Education; Program Content; Program Effectiveness; Refrigeration; Solar Energy; Technical Education; Trade and Industrial Education; Ventilation; Welding; Florida; Reports, Evaluative; Guides, Classroom -- Teacher